PENYULUHAN DALAM UPAYA PENCEGAHAN COVID-19 DENGAN PENYEMPROTAN DISINFEKTAN DAN PENERAPAN ATURAN KESEHATAN DI DESA PAKUTANDANG, KECAMATAN CIPARAY, KABUPATEN BANDUNG - Yulina, Henly; Yusdian, Yudi; Kantikowati, Endang; Karya, Karya; Minangsih, Dian Murti; Santoso, Joko; Kundrat, Kundrat; Herdiana, Yudi; Yuspita, Widdy (Jurnal Abdi Inovatif : Pengabdian kepada Masyarakat, 2024)
Corona Virus Disease 2019 (COVID-19) is a new type of disease that has never been identified in humans. This disease infects the respiratory tract and is usually transmitted through close physical contact and respiratory droplets. This community service activity aims to increase knowledge and insight among participants regarding the importance of maintaining and following health regulations to minimize and stop the spread of COVID-19 and realize changes in healthy behavior during the pandemic. The methods used are counseling, simulation, and evaluation methods. Before carrying out this activity, socialization was carried out first by visiting the Pakutandang Village office, meeting and discussing with the Pakutandang Village Head regarding the needs that could be provided to minimize and stop the spread of COVID-19, and asking for permission to carry out community service activities. The results of the service show that the service activities went smoothly. Participants participate actively and collaboratively in discussion and question-and-answer activities. This service activity increases and broadens the knowledge and perspectives of the participants, including lecturers at Bale Bandung University, village heads, and government officials from the Pakutandang Village Office, students at the Faculty of Agriculture, Bale Bandung University, residents of Pakutandang Village and the COVID-19 task force in Ciparay District. Thus, the participants understood the importance of following health regulations and continuous spraying of disinfectants in the school and home environment around Pakutandang Village in implementing healthy behavior changes during the pandemic. The activity results will enable the implementation of good habits in complying with health protocols in the school and home environment, especially in Pakutandang Village, Ciparay District.